The Effect of Cooperative Group Work and Assessment on the Attitudes of Students towards Science in New Zealand - Lowe, John Paul (Curtin University, 2004)
The improvement of secondary-level students’ attitude to science is encouraged in the New Zealand curriculum document. It is also noteworthy that employers in scientific institutions and commercial organisations place great value on group or teamwork. However, it is apparent that some teachers have reservations about cooperative group work, particularly problems with classroom management. There has been significant research done on cooperative learning and student attitudes, but investigations about the use of cooperative group work to improve the science-related attitudes of our younger secondary school students are rare. This thesis focuses on the effect of cooperative group work and assessment on the attitudes of 312 science students in four rural secondary schools in New Zealand. The cooperative groups were established using a simplified protocol which was non intrusive on curriculum delivery to help ensure wide acceptance by secondary science teachers. The students’ attitudes were assessed quantitatively using the Test of Science Related Attitudes (TOSRA) while qualitative results were obtained through teacher and student interviews along with researcher observations.. The data were collected before and after three terms of cooperative learning in a variety of activities including practical classes, fieldwork, and written assignments and class tests. This part of the study revealed that group work and group assessment enhanced students’ attitudes to science, with both the teachers and students seeing real value in such activities, especially the formative group testing opportunities. The study also confirmed the reliability and validity of the TOSRA in New Zealand schools for the first time.The TOSRA was also used to make comparisons of the science-related attitudes of several subgroups within the study population. Such comparisons included the effects of gender, grade level and band along with consideration of the roles of the teacher and classroom environment on student attitudes. Finally, a teacher friendly set of guidelines for the implementation of cooperative group work and assessment in the classroom has been prepared as result of this ongoing research.